Regulation of insect behavior via the insulin-signaling pathway - Erion, Renske; Sehgal, Amita (Frontiers in Physiology, 2013)
The insulin/insulin-like growth factor signaling (IIS) pathway is well established as a critical regulator of growth and metabolic homeostasis across the animal kingdom. Insulin-like peptides (ILPs), the functional analogs of mammalian insulin, were initially discovered in the silkmoth Bombyx mori and subsequently identified in many other insect species. Initial research focused on the role of insulin signaling in metabolism, cell proliferation, development, reproduction and aging. More recently however, increasing attention has been given to the role of insulin in the regulation of neuronal function and behavior. Here we review the role of insulin signaling in two specific insect behaviors: feeding and locomotion.